Molecular, epidemiological, haematological and biochemical evaluation in asymptomatic Theileria annulata infected cattle from an endemic region in Spain - Calleja Bueno, Lydia; Sainz, Ángel; García Sancho, Mercedes; Rodríguez Franco, Fernando; González Martín, Juan V.; Villaescusa, Alejandra (My University, 2017)
Mediterranean theileriosis is one of the most fatal theilerioses, with considerable economic impact on livestock production. The potential consequences of asymptomatic infection on the animal¿s health and on the epide miology in endemic regions are still unclear. The objectives of this study were to determine the molecular prevalence of T. annulata in a representative population of asymptomatic cattle in extensive management in Madrid, Central Spain, an area where practitioners frequently report cases of clinical theileriosis, and to evaluate the existence of associations between infection by this pathogen and haematological, biochemical and epide miological data. T. annulata DNA was detected in 22.4% of the study population. The age was statistically associated with T. annulata prevalence rates, with a higher prevalence in cows older than 8 years (26.1%). Introduction of new cattle to the farm, grazing on pastures with other herds of cattle and previous history of clinical cases were statistically related to a higher prevalence of T. annulata infection. Herds with more than one ectoparasiticide treatment per year and that used more than one drug had significantly lower prevalences of infection with T. annulata. The location of farms in areas with a mean temperature higher than 17.1° C and mean altitude lower than 962 m was statistically associated with the presence of T. annulata. In our study, the mean values of haematological parameters were within the normal adult range, but it is noteworthy that some T. annulata-infected animals presented low values for red blood cell parameters